2022
DOI: 10.1021/acs.orglett.2c00491
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Allene Formation via Alkyne Tautomerization to Promote [4 + 2]-Cycloadditions with a Pendant Alkyne or Nitrile

Abstract: We have explored the net-[4 + 2]-cycloadditions of a variety of aryl (or alkenyl) alkynes. Tautomerization via base-catalyzed alkyne-to-allene isomerization produces a transient allene, which undergoes stepwise cyclization with not only a pendant alkyne but also a nitrile. The operative mechanisms for these reactions were studied by density functional theory and compared with the slower thermal cyclization of the precursor alkyne.Letter pubs.acs.org/OrgLett

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…We had also examined 11a in our earlier study, but the intermediate allene was not observed in that instance as well. 5 These results implied that the rate-limiting step for these reactions is the generation of the allenes and not the subsequent, more rapid cyclization events.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…We had also examined 11a in our earlier study, but the intermediate allene was not observed in that instance as well. 5 These results implied that the rate-limiting step for these reactions is the generation of the allenes and not the subsequent, more rapid cyclization events.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…These observations were consistent with the reactivity we previously reported for the gem-dimethylated analogs of 11b−11d and are reflective of a slower tautomerization to the requisite allene intermediates 12. 5 To better understand the energetic differences required to achieve the cyclization of 11a vs 11b, we undertook density functional theory (DFT) calculations. We were unable to find a concerted transition state structure (TSS) connecting either of the allenes 12 with its corresponding dearomatized intermediate 15.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations